2012
DOI: 10.4049/jimmunol.1102432
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown in Repression of IFN-γ mRNA Leads to Accumulation of Self-Reactive Effector CD8+ T Cells

Abstract: Tight regulation of virus-induced cytotoxic effector CD8+ T cells is essential to prevent immunopathology. Naturally occurring effector CD8+ T cells, with a KLRG1hi CD62Llo phenotype typical of short-lived effector CD8+ T cells (SLECs), can be found in increased numbers in autoimmune-prone mice, most notably in mice homozygous for the san allele of Roquin. These SLEC-like cells were able to trigger autoimmune diabetes in a susceptible background. When Roquin is mutated (Roquinsan), effector CD8+ T cells accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…This is consistent with the finding of a population of SLECs in the spleen of Rc3h1 −/− mice [6]. Similar findings linked to increased IFN-γ synthesis have been described for Roquin san/san mice [26]. Additional studies are planned in our laboratory using adoptive transfer experiments to trace the homing properties of the Roquin san/san SLECs to the gut, and using IL-7R expression to differentiate MLN SLECs from memory precursor effector cells (MPECs) [27].…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the finding of a population of SLECs in the spleen of Rc3h1 −/− mice [6]. Similar findings linked to increased IFN-γ synthesis have been described for Roquin san/san mice [26]. Additional studies are planned in our laboratory using adoptive transfer experiments to trace the homing properties of the Roquin san/san SLECs to the gut, and using IL-7R expression to differentiate MLN SLECs from memory precursor effector cells (MPECs) [27].…”
Section: Discussionsupporting
confidence: 85%
“…Both IL-2 21,3941 and IFN-γ 42,43 have been shown to individually program GzmB expression in T cells, and our current data extend these findings by demonstrating that these two cytokines can cooperate to program maximal GzmB expression. Somewhat paradoxically, however, IFN-γ controls the responsiveness of these effector T cells to IL-2 by limiting the expression of the IL-2 receptor alpha chain (CD25) that confers high affinity binding.…”
Section: Discussionsupporting
confidence: 83%
“…Both IL-2 21,3941 and IFN-γ 42,43 can program T cells to express GzmB. Our current data indicate that the two cytokines cooperate in dual-costimulated T cells to program maximal GzmB expression (Figure 1b).…”
Section: Resultsmentioning
confidence: 52%
“…So, decreased KLRG1 + cell numbers could reflect the actions of the Tregs to reduce the IL-12 driven autoimmune process which is critical to the dnTGFβRII model [34,35]. Excess IFNγ can also drive the expression of frankly autoreactive KLRG1 + CD8 T cells, as shown by the increased numbers of these cells in mice expressing the sanroquin mutation of Roquin [36]. Finally, recent studies in tumor immunology have shown that KLRG1 + CD8 cells are cytotoxic to tumor tissue [3739], supporting the hypothesis that KLRG1 + CD8 cells may mediate hepatic autoimmunity by causing cholangiocyte cell death.…”
Section: Discussionmentioning
confidence: 99%